Ovarian cancer risk management in BRCA-mutation carriers: A comparison of six international and national guidelines. (November 2022) - Matan, Liat S; Perri, Tamar; Kogan, Liron; Brandt, Benny; Meyer, Raanan; Levin, Gabriel
Abstract: Objective: Germline mutations in the BRCA gene account for most hereditary ovarian and breast cancer. Management of healthy carriers aims to prevent and allow early detection of breast and ovarian cancer. This study compares six different hereditary ovarian cancer management guidelines, highlighting areas of controversy between different societies. We aim to compare international and national guidelines regarding BRCA carriers' management. Study design: A comparative study. We retrieved, reviewed, and compared the most recent guidelines of BRCA mutation carriers from the specializing societies NCCN (National Comprehensive National network) and ESMO (European society of medical oncology), and national societies of the United States (American College of Obstetricians and Gynecologists), England (the Royal College of Obstetricians and Gynecologists), Canada (the Society of Obstetricians and Gynaecologists of Canada) and Spain (Sociedad Española de Oncología Médica). Results: There is a broad consensus regarding the limited role of screening for early ovarian cancer detection (4 out of 6) (4/6) and regarding the recommendation for implementation of Risk-reducing salpingo-oophorectomy (RRSO) (6/6), some variations exist for age at RRSO. It is widely accepted that risk reducing salpingectomy should be performed only as part of research (5/6), and that the addition of risk-reducing hysterectomy should be individualized (3/6). Not all guidelines address fertility issues, and controversy exists regarding hormone replacement therapy (HRT) recommendations in unaffected young BRCA-mutation carriers following RRSO. Conclusion: BRCA carrier's management guidelines consist of well-agreed topics such as the ineffective screening for early detection of ovarian cancer and the recommendation of RRSO. HRT remains controversial. Conforming unified recommendations is needed for providing evidence-based recommendations.